Emergence of white organic light-emitting diodes based on thermally activated delayed fluorescence - Xiao, Peng (2018)
Recently, thermally activated delayed fluorescence (TADF) organic light-emitting diodes (OLEDs) have attracted both academic and industrial interest due to their extraordinary characteristics, such as high efficiency, low driving voltage, bright luminance, lower power consumption and potentially long lifetime. In this invited review, the fundamental concepts of TADF have been firstly introduced. Then, main approaches to realize WOLEDs based on TADF have been summarized. More specifically, the recent development of WOLEDs based on all TADF emitters, WOLEDs based on TADF and conventional fluorescence emitters, hybrid WOLEDs based on blue TADF and phosphorescence emitters and WOLEDs based on TADF exciplex host and phosphorescence dopants is highlighted. In particular, design strategies, device structures, working mechanisms and electroluminescent processes of the representative WOLEDs based on TADF are reviewed. Finally, challenges and opportunities for further enhancement of the performance of WOLEDs based on TADF are presented.